Growth and development of the kazakh national dance culture (Journal of Philosophy Culture and Political Science, 2018)
Dance Arts – one of the most important sources of national culture. For this reason, dance, affecting the world, has become a cultural value. It is based on the concept of artistic self-discovery, self-awareness and self-acceptance of people. According to the art of dance we are able to judge the spiritual and artistic values of the features of any nation. This original source, the original quality of the people is the art of it. Any people through art can determine their original philosophical system. Every nation art, life and feelings cognitionclosely linked. We can say that the Kazakh people formed his spiritual culture on the basis of figurative art concepts. The aim of this work is the comparative study of traditions and innovations in dance culture of the Kazakh and Turkish peoples, the revival of the old classical dance movements and on this basis to form the youth harmonious aesthetic perception of dance. In addition, the dissertation seeks to instill in the younger generation a sense of patriotism, love for the country, morality, beauty of body and soul.Key words: еnsemble, repertoire, image, art, composition, dance, choreography.